A method and system for producing molybdenum oxide
By using the combined technology of composite ammonium dimodate dimodate material and porous polymer in molybdenum oxide production, the efficient production of high-purity molybdenum oxide under low temperature conditions is achieved, and the problems of high energy consumption and environmental pollution in the traditional high-temperature roasting method are solved.
Patent Information
- Application Number
- CN202410934074.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-12
AI Technical Summary
In the existing molybdenum oxide production technology, the energy consumption of high temperature roasting method is high, resulting in an increase in production costs, and the valuable elements are easily evaporated under high temperature conditions, reducing the product recovery rate, and the waste gas and waste slag generated at the same time pollute the environment.
A molybdenum oxide production method is adopted to achieve high purity production of molybdenum oxide by calcining the composite ammonium dimodate material in a rotary kiln at low temperature, combining the support effect of the porous polymer and the stability of the tartaric acid-molybdenum complex.
Decomposed of composite ammonium dimolybdate at a lower temperature improves energy efficiency, reduces production costs, and improves the purity and dispersion of molybdenum oxide through the support structure of the porous polymer, and the obtained molybdenum oxide purity is greater than 99%.
Smart Images

Figure CN118929756B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molybdenum oxide materials, and in particular to a molybdenum oxide production method and a production system thereof. Background Art
[0002] The chemical formula of molybdenum trioxide is MoO3, the molecular weight is about 143.958, its appearance is colorless to yellow-white crystalline powder, the melting point is 795℃, the boiling point is 1155℃, and the density is 4.692g / cm 3 . Molybdenum trioxide is stable in the air, soluble in concentrated nitric acid and concentrated hydrochloric acid, and exhibits high chemical activity. Molybdenum trioxide is composed of MoO6 octahedron as the basic structural unit, which forms a chain structure through corner-sharing connection, and further forms a layered structure through edge-sharing connection. The layers are stacked on each other by van der Waals forces, making molybdenum trioxide an ideal material in many high-tech fields. In the field of catalysis, molybdenum trioxide, as a catalyst, promotes chemical reactions and significantly improves the yield and reaction rate, especially playing an important role in the petroleum industry and the preparation of organic compounds. At the same time, with the increasing demand for clean energy, the application of molybdenum trioxide in technologies such as fuel cells and photocatalytic water decomposition has also received increasing attention. In the field of materials science, molybdenum trioxide is used to prepare a variety of high-performance materials due to its good electrical conductivity and thermal conductivity. In addition, in the metallurgical and glass industries, molybdenum trioxide also shows its unique application potential.
[0003] In the existing molybdenum oxide production technology, the traditional production method mainly adopts a high-temperature roasting method, that is, the molybdenum concentrate is oxidatively roasted at high temperature to obtain a molybdenum oxide product. However, the high-temperature roasting process has high energy consumption, which leads to increased production costs. Secondly, under high temperature conditions, the valuable elements in the molybdenum ore are easily volatilized, thereby reducing the recovery rate of the product. In addition, the waste gas and waste residue generated by the traditional method cause great pollution to the environment and have high processing costs. For example, the invention patent with patent publication number CN106517331A discloses a method for preparing powdered amorphous molybdenum oxide, in which an ammonium molybdate aqueous solution is added to a solution containing butyl titanate, ethanol, n-butanol and naringin at 450-600°C and under stirring. After stirring and aging, the resulting precipitate is separated, dried, and calcined to obtain a powdered amorphous molybdenum oxide containing titanium. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a molybdenum oxide production method and a production system thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A molybdenum oxide production system comprises a rotary kiln, wherein the rotary kiln is provided with a bucket elevator, the bucket elevator is used for conveying a composite ammonium dimolybdate material to the rotary kiln, the rotary kiln is also fixedly connected to a mixing hopper, a monorail is provided on the top of the mixing hopper, the mixing hopper is used for manually adding the composite ammonium dimolybdate material, the discharge end of the rotary kiln is connected to the feed end of a vibrating screen machine, the discharge end of the vibrating screen machine is connected to the feed end of a molybdenum oxide silo, a second gas collecting hood is provided on the top of the molybdenum oxide silo, the discharge end of the molybdenum oxide silo is connected to the feed end of a molybdenum oxide mixer, the molybdenum oxide silo is also provided with a leaching device and a filtering device, the molybdenum oxide mixer is also provided with a drying device, a first gas collecting hood is provided on the top of the mixing hopper, the first gas collecting hood is used for collecting ammonia and smoke generated by the rotary kiln, and the rotary kiln, the vibrating screen machine, the molybdenum oxide silo and the molybdenum oxide mixer are connected through a pipeline.
[0007] According to another aspect of the present invention, there is provided a method for producing molybdenum oxide, comprising the following steps:
[0008] The composite ammonium dimolybdate material is placed in a rotary kiln and calcined at low temperature for 4-6 hours. The calcined product is filtered and sieved by a vibrating sieve machine before being passed into a molybdenum oxide silo. It is alternately rinsed with deionized water and ethanol for 20-30 minutes, filtered, and passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide.
[0009] The main reaction equation for calcination is:
[0010] (NH4)2Mo2O7=2MoO3+H2O↑+2NH3↑
[0011] Furthermore, the composite ammonium dimolybdate material is prepared by the following steps:
[0012] S1. Add tartaric acid to deionized water, heat and stir for 10-20 min, then slowly add ammonium dimolybdate, stir for 30-60 min, and let stand at room temperature for 4-6 h to obtain a complex solution;
[0013] S2, adding polyethylene glycol and acrylic acid to deionized water, adding ammonium persulfate and N,N'-methylenebisacrylamide under stirring, placing in a constant temperature oil bath, controlling the reaction temperature to 60-80°C, reacting for 4-8h, cooling to room temperature, filtering, and vacuum drying at 40-60°C to constant weight to obtain a porous polymer;
[0014] S3. Add the porous polymer into deionized water, perform ultrasonic treatment for 5-15 minutes to obtain a porous polymer suspension, add the complex solution into the porous polymer suspension, continue stirring for 1-2 hours, and obtain a composite ammonium dimolybdate material.
[0015] Furthermore, the calcination temperature is 250-350°C, and the heating rate is 5-10°C / min.
[0016] Furthermore, in step S1, the heating temperature is 40-50° C., the first stirring speed is 100-300 rpm, and the second stirring speed is 200-400 rpm.
[0017] Furthermore, in step S1, the mass ratio of tartaric acid, deionized water and ammonium dimolybdate is (4-8): (50-100): (6-10).
[0018] Furthermore, in step S2, the mass ratio of polyethylene glycol, acrylic acid, deionized water, ammonium persulfate and N,N'-methylenebisacrylamide is (4-7):(3-6):(30-50):(0.1-0.5):(0.04-0.1).
[0019] Furthermore, in step S3, the mass ratio of the complex solution to the porous polymer suspension is (1-2): (0.5-0.8).
[0020] Furthermore, the frequency of the ultrasonic treatment in step S3 is 30-40kHz, and the power is 200-300W.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. In the technical solution of the present invention, tartaric acid forms a stable complex with the molybdenum ion in ammonium dimolybdate, and the two carboxyl oxygen atoms in the tartaric acid molecule form a bidentate coordination with a molybdenum ion to form a stable five-membered ring structure, which is more stable than ammonium dimolybdate alone. Therefore, it can be decomposed at a lower temperature to release molybdenum oxide, avoiding the energy consumption required for high-temperature calcination, improving the overall energy efficiency, and reducing production costs.
[0023] 2. In the technical solution of the present invention, the porous polymer is used as a support, and its high specific surface area and ordered pore structure provide sufficient dispersion space for the tartaric acid-molybdenum complex. During the calcination process, the pore structure of the porous polymer can limit the growth and agglomeration of molybdenum oxide particles, and can effectively prevent the agglomeration of molybdenum oxide particles, so that the final product has higher purity and better dispersibility.
[0024] 3. Through the complexation of tartaric acid and ammonium dimolybdate, and the support of porous polymers, the complexation makes it difficult for molybdenum ions to migrate and agglomerate during the calcination process, while the support of porous polymers limits the growth and deformation of molybdenum oxide particles. The composite ammonium dimolybdate material can maintain structural stability during the calcination process, which helps to reduce structural defects and impurity phases generated during the calcination process. The obtained molybdenum oxide product has better structural integrity and stability, and the purity is greater than 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 A structural block diagram of a molybdenum oxide production system of the present invention;
[0027] Figure 2 The present invention is a flowchart of a method for producing molybdenum oxide.
[0028] In the figure: 1. bucket elevator; 2. rotary kiln; 3. vibrating screen; 4. molybdenum oxide silo; 5. molybdenum oxide mixer; 6. mixing hopper; 7. monorail; 8. gas collecting hood 1; 9. gas collecting hood 2. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Preparation Example 1
[0031] The composite ammonium dimolybdate material comprises the following steps to prepare:
[0032] S1, add 400g tartaric acid to 5000g deionized water, heat to 40°C, stir for 10min at 100rpm, then slowly add 600g ammonium dimolybdate, stir for 30min at 200rpm, and let stand at room temperature for 4h to obtain a complex solution;
[0033] S2, adding 400g polyethylene glycol and 300g acrylic acid to 3000g deionized water, adding 10g ammonium persulfate and 4g N,N'-methylenebisacrylamide under stirring, placing in a constant temperature oil bath, controlling the reaction temperature to 60°C, reacting for 4h, cooling to room temperature, filtering, and vacuum drying at 40-60°C to constant weight to obtain a porous polymer;
[0034] S3. Add the porous polymer into deionized water and perform ultrasonic treatment for 5 minutes. The frequency of the ultrasonic treatment is 30 kHz and the power is 200 W to obtain a porous polymer suspension. Add 100 g of the complex solution into 50 g of the porous polymer suspension and continue stirring for 1 hour to obtain a composite ammonium dimolybdate material.
[0035] Preparation Example 2
[0036] The composite ammonium dimolybdate material comprises the following steps to prepare:
[0037] S1, add 550g of tartaric acid to 7500g of deionized water, heat to 45°C, stir for the first time at a speed of 200rpm for 15min, then slowly add 800g of ammonium dimolybdate, stir for the second time at a speed of 300rpm for 45min, and let stand at room temperature for 5h to obtain a complex solution;
[0038] S2, adding 550g polyethylene glycol and 450g acrylic acid to 4000g deionized water, adding 30g ammonium persulfate and 7g N,N'-methylenebisacrylamide under stirring, placing in a constant temperature oil bath, controlling the reaction temperature to 70°C, reacting for 6h, cooling to room temperature, filtering, and vacuum drying at 50°C to constant weight to obtain a porous polymer;
[0039] S3. Add the porous polymer into deionized water and perform ultrasonic treatment for 10 minutes. The frequency of the ultrasonic treatment is 35 kHz and the power is 250 W to obtain a porous polymer suspension. Add 150 g of the complex solution into 65 g of the porous polymer suspension and continue stirring for 1.5 hours to obtain a composite ammonium dimolybdate material.
[0040] Preparation Example 3
[0041] The composite ammonium dimolybdate material comprises the following steps to prepare:
[0042] S1. Add 700 g of tartaric acid to 10000 g of deionized water, heat to 50° C., stir for 20 min at 300 rpm, then slowly add 1000 g of ammonium dimolybdate, stir for 60 min at 400 rpm, and let stand at room temperature for 6 h to obtain a complex solution;
[0043] S2, adding 700g polyethylene glycol and 600g acrylic acid to 5000g deionized water, adding 50g ammonium persulfate and 10g N,N'-methylenebisacrylamide under stirring, placing in a constant temperature oil bath, controlling the reaction temperature to 80°C, reacting for 8h, cooling to room temperature, filtering, and vacuum drying at 60°C to constant weight to obtain a porous polymer;
[0044] S3. Add the porous polymer into deionized water and perform ultrasonic treatment for 15 minutes. The frequency of the ultrasonic treatment is 40 kHz and the power is 300 W to obtain a porous polymer suspension. Add 200 g of the complex solution into 80 g of the porous polymer suspension and continue stirring for 2 hours to obtain a composite ammonium dimolybdate material.
[0045] Example 1
[0046] 50 kg of the composite ammonium dimolybdate material obtained in Preparation Example 1 was placed in a rotary kiln, the heating rate was set to 5°C / min, and low-temperature calcination was carried out at 250°C for 4 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, rinsed alternately with deionized water and ethanol for 20 minutes, filtered, and passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.54%.
[0047] Example 2
[0048] 50 kg of the composite ammonium dimolybdate material obtained in Preparation Example 1 was placed in a rotary kiln, the heating rate was set to 5°C / min, and low-temperature calcination was carried out at 280°C for 6 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, and rinsed alternately with deionized water and ethanol for 30 minutes. After filtering, it was passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.67%.
[0049] Example 3
[0050] 50 kg of composite ammonium dimolybdate material obtained in Preparation Example 2 was placed in a rotary kiln, the heating rate was set to 8°C / min, and low-temperature calcination was carried out at 300°C for 5 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, and rinsed with deionized water and ethanol alternately for 25 minutes. After filtering, it was passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.72%.
[0051] Example 4
[0052] 50 kg of composite ammonium dimolybdate material obtained in Preparation Example 2 was placed in a rotary kiln, the heating rate was set to 5°C / min, and low-temperature calcination was carried out at 310°C for 6 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, and rinsed with deionized water and ethanol alternately for 30 minutes. After filtering, it was passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.70%.
[0053] Example 5
[0054] 50 kg of composite ammonium dimolybdate material obtained in Preparation Example 3 was placed in a rotary kiln, the heating rate was set to 10°C / min, and low-temperature calcination was carried out at 330°C for 6 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, rinsed alternately with deionized water and ethanol for 30 minutes, filtered, and passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.63%.
[0055] Example 6
[0056] 50 kg of the composite ammonium dimolybdate material obtained in Preparation Example 3 was placed in a rotary kiln, the heating rate was set to 10°C / min, and low-temperature calcination was carried out at 350°C for 6 hours. The calcined product was filtered and sieved by a vibrating sieve machine and then passed into a molybdenum oxide silo, and rinsed alternately with deionized water and ethanol for 30 minutes. After filtering, it was passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide with a purity of 99.78%.
[0057] Comparative Example 1
[0058] The difference between this comparative example and Example 1 is that commercially available ammonium dimolybdate is used instead of the composite ammonium dimolybdate material, and the remaining steps are the same as those in Example 1. The purity of the obtained molybdenum oxide is 98.40%.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 2 is that the complex solution prepared in step S1 of Preparation Example 2 is used instead of the composite ammonium dimolybdate material, and the remaining steps are the same as those in Example 2. The purity of the obtained molybdenum oxide is 96.92%.
[0061] Comparative Example 3
[0062] The difference between this comparative example and Example 3 is that the calcination temperature is 200° C., and the remaining steps are the same as those in Example 3. The purity of the obtained molybdenum oxide is 62.41%.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 3 is that the calcination temperature is 180° C., and the remaining steps are the same as those in Example 3. The purity of the obtained molybdenum oxide is 34.33%.
[0065] Comparative Example 5
[0066] The difference between this comparative example and Example 3 is that the calcination temperature is 400° C., and the remaining steps are the same as those in Example 3. The purity of the obtained molybdenum oxide is 98.86%.
[0067] Comparative Example 6
[0068] The difference between this comparative example and Example 3 is that the calcination temperature is 500° C., and the remaining steps are the same as those in Example 3. The purity of the obtained molybdenum oxide is 98.54%.
[0069] As can be seen from Examples 1-6, the composite ammonium dimolybdate material can significantly improve the purity of molybdenum oxide under suitable calcination conditions. The porous polymer in the composite material can limit the growth and agglomeration of molybdenum oxide particles, making the molybdenum oxide particles in the calcined product more uniform and fine, thereby improving the purity. At the same time, the stability of the complex also helps to maintain the stability of molybdenum oxide during the calcination process, further improving the purity.
[0070] It can be seen from Comparative Examples 1-2 that the purity of molybdenum oxide obtained by calcining using commercially available ammonium dimolybdate or a single complex solution is low. Commercially available ammonium dimolybdate may be unstable, and the single complex solution is prone to particle agglomeration during the calcination process, resulting in reduced purity. In Comparative Examples 3-4, too low a calcination temperature will cause the purity of molybdenum oxide to be significantly reduced. Too low a temperature cannot completely decompose the complex, resulting in a large amount of undecomposed complexes and impurities in the calcined product. In Comparative Examples 5-6, although too high a calcination temperature can obtain a higher purity molybdenum oxide, its energy consumption is significantly increased compared to the appropriate temperature in the embodiment.
[0071] In summary, the porous polymer and complex in the composites improve purity and reduce energy consumption by limiting particle growth and agglomeration and maintaining the stability of molybdenum oxide during calcination, respectively.
[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for producing molybdenum oxide, characterized in that: The following steps are involved: The composite ammonium dimolybdate material is placed in a rotary kiln and calcined at low temperature for 4-6 hours. The calcined product is vibrated by a vibrating screener and then passed into a molybdenum oxide silo. It is alternately rinsed with deionized water and ethanol for 20-30 minutes, filtered, and then passed into a molybdenum oxide mixer for drying to obtain high-purity molybdenum oxide. Wherein, the composite ammonium dimolybdate material comprises the following steps to prepare: S1. Add tartaric acid to deionized water, heat and stir for 10-20 min, then slowly add ammonium dimolybdate, stir for 30-60 min, and let stand at room temperature for 4-6 h to obtain a complex solution; S2, adding polyethylene glycol and acrylic acid to deionized water, adding ammonium persulfate and N,N'-methylenebisacrylamide under stirring, placing in a constant temperature oil bath, controlling the reaction temperature to 60-80°C, reacting for 4-8h, cooling to room temperature, filtering, and vacuum drying at 40-60°C to constant weight to obtain a porous polymer; S3. Add the porous polymer into deionized water, perform ultrasonic treatment for 5-15 minutes to obtain a porous polymer suspension, add the complex solution into the porous polymer suspension, continue stirring for 1-2 hours, and obtain a composite ammonium dimolybdate material.
2. A method for producing molybdenum oxide according to claim 1, characterized in that: The calcination temperature is 250-350°C, and the heating rate is 5-10°C / min.
3. A method for producing molybdenum oxide according to claim 1, characterized in that: In step S1, the heating temperature is 40-50° C., the first stirring speed is 100-300 rpm, and the second stirring speed is 200-400 rpm.
4. A method for producing molybdenum oxide according to claim 1, characterized in that: The mass ratio of tartaric acid, deionized water and ammonium dimolybdate in step S1 is (4-8): (50-100): (6-10).
5. A method for producing molybdenum oxide according to claim 1, characterized in that: In step S2, the mass ratio of polyethylene glycol, acrylic acid, deionized water, ammonium persulfate and N,N'-methylenebisacrylamide is (4-7): (3-6): (30-50): (0.1-0.5): (0.04-0.1).
6. A method for producing molybdenum oxide according to claim 1, characterized in that: In step S3, the mass ratio of the complex solution to the porous polymer suspension is (1-2): (0.5-0.8).
7. A method for producing molybdenum oxide according to claim 1, characterized in that: The frequency of the ultrasonic treatment in step S3 is 30-40kHz and the power is 200-300W.
Citation Information
Patent Citations
Preparation method of molybdenum oxide
CN106517331A
Porous carbon-loaded molybdenum oxide nanoparticle composite material and preparation method thereof
CN106976910A
Method for producing high-solubility molybdenum trioxide for catalyst from molybdenum concentrate
CN108046325A